Les principes de Nüremberg et l'évolution du droit international - Klafkowski, Alfons (Warszawa : Zachodnia Agencja Prasowa, 1966)
Bibliotheek Camille Huysmans
Frans
Brochure
Keywords: internationaal recht; oorlogsmisdaden; oorlogsslachtoffers